Pursuing an Innovative Development Pathway : Understanding China’s NDC - Partnership for Market Readiness; National Center for Climate Change Strategy and International Cooperation (World Bank, Washington, DC, 2016)
This report was prepared as part of the Partnership for Market Readiness (PMR) Policy Analysis Work Program which was launched to support countries’ efforts to determine post-2020 mitigation scenarios and identify packages of effective and cost-efficient policies—including carbon pricing instruments—to achieve climate change mitigation. This report contributed to the development of the China’s Nationally Determined Contribution (NDC) and facilitated the process of presenting and disclosing the key indicators, components, and assumptions that are used for the mid- and long-term scenarios. The report also improves understanding on how China’s NDC could be seen as a powerful vehicle for innovation and help shift the country toward a new development pathway.